Effect of Heat Input on Microstructure and Mechanical Properties of Submerged Arc Welded SM570-TMC Steel - Yuhandri, Toni; Winarto, Winarto; Natalia, Diana (Journal of Materials Exploration and Findings, 2023)
SM570TMC is high-strength steel (HSS), which is commonly used in structures that require higher-strength components. In this research, submerged arc welding (SAW)-welded SM570 TMC steels' microstructure and mechanical characteristics were examined. SM570 plates with 12mm thickness were multi-pass welded by using a 3.0 mm diameter of ESAB OK Autrod 13.40 (AWS A5.23: EG) filler metal. The joint design is a single V multi-pass butt weld with a backing strip. Two welded joints were prepared by using heat inputs of 2.2 and 2.9 kJ/mm. The microstructures of two welded joints were observed by using optical microscopy and scanning electron microscope (SEM). Hardness tests were performed in the weld metal, heat-affected zone, and base metal. The mechanical properties of welded joints were assessed using the tensile test and Charpy V notch impact test in HAZ and weld metal areas. The result showed that the strength of joints is satisfactory with no fracture in weld metal while the impact energy of weld metal and HAZ is acceptable for lower temperature application.